2014
DOI: 10.1097/yct.0b013e182a2705d
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of a 24-Year-Old Man With Resolution of Treatment-Resistant Major Depressive Disorder and Comorbid PTSD Using rTMS

Abstract: Although there is a large amount of literature indicating the effectiveness of repetitive transcranial magnetic stimulation (rTMS) for treatment-resistant major depressive disorder (trMDD), the authors did not find any literature supporting rTMS for MDD with the comorbid condition of posttraumatic stress disorder (PTSD). Here, we report an original case of a patient whose trMDD and PTSD remitted using rTMS at the left dorsolateral prefrontal cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Several unblinded studies have examined left-sided high-frequency TMS for patients with both MDD and PTSD considering the very high rate of comorbidity, and have consistently found improvements not only in depressive but also in PTSD symptoms. In one case report, 41 a standard 10 Hz depression protocol was applied to an individual with comorbid PTSD and MDD, and this led to remission on both the Beck Depression Inventory (BDI 50 ) and the PCL. Building on prior work that showed efficacy of an intermediate stimulation frequency of 5 Hz for both depression and anxiety symptoms, two studies found significant improvement in both depression and PTSD with left-sided 5 Hz TMS.…”
Section: Tms Monotherapymentioning
confidence: 99%
“…Several unblinded studies have examined left-sided high-frequency TMS for patients with both MDD and PTSD considering the very high rate of comorbidity, and have consistently found improvements not only in depressive but also in PTSD symptoms. In one case report, 41 a standard 10 Hz depression protocol was applied to an individual with comorbid PTSD and MDD, and this led to remission on both the Beck Depression Inventory (BDI 50 ) and the PCL. Building on prior work that showed efficacy of an intermediate stimulation frequency of 5 Hz for both depression and anxiety symptoms, two studies found significant improvement in both depression and PTSD with left-sided 5 Hz TMS.…”
Section: Tms Monotherapymentioning
confidence: 99%
“…Gene array analyses of post-mortem tissue show dysregulated mitochondrial function in the dlPFC of patients with PTSD ( Su et al., 2008 ). Preliminary evidence suggests that rTMS to strengthen left dlPFC may aid treatment of PTSD, at least in those with depression ( Nakama et al., 2014 ). Functional imaging has also shown altered patterns of PFC activity to emotional charged words in abused women with PTSD ( Bremner et al., 2003 ), although the pattern of changes was more complex.…”
Section: Role Of Dlpfc Dysfunction In Ptsdmentioning
confidence: 99%
“…With this rationale, several studies evaluated the feasibility and the clinical benefits of using TMS or tDCS alone or combined with psychotherapy. In this review, we evaluated 13 RCTs [9,10,18,[21][22][23][24][25][26][27][28][29][30], 11 case series [8,[31][32][33][34][35][36][37][38][39][40], and 6 case reports [7,21,[41][42][43][44] on neuromodulation for PTSD, focusing on TMS, tDCS, and DBS. Details of the articles pooled for analysis in our review are summarized in Tables 1 (TMS), 2 (tDCS), and 3 (DBS).…”
Section: Resultsmentioning
confidence: 99%